Characteristics of gamma radiation fields in subterranean structures for radiation protection and decision making - Parker, Alex R., author; Brandl, Alexander, advisor; Johnson, Thomas E., committee member; Lindsay, James, committee member (Colorado State University. Libraries, 2022)
The threat of a CBRN attack or accident within subterranean space presents unique challenges for decision makers and emergency planners due to the operational constraints imposed by the physical environment. Radiological exposure device threat scenarios have not previously been explored for vulnerable subsurface infrastructure, like mass transit tunnels. It is important to investigate the impact that radiation exposure devices could have in these types of environments because radiation fields from gamma ray emitting sources behave peculiarly in well shielded and confined spaces where radiation scattering is substantial. This project began with benchmark measurements of a Cs-137 source in several different well shielded, small scale tunnel geometries as a proof of concept study demonstrating the complexity of radiation fields in such environments. Follow on calculations utilizing the radiation transport code, MCNP®, confirmed that the high scattering environment results in apparent radiation streaming down the length of the tunnel, where the calculated dose rates are higher than observed in a free field at equivalent distances. The tunnel material also proved important for the impact of radiation scattering, implying that there is an optimization between the probability of scattering and self-absorption in walls. Other simulated tunnel geometries confirmed the presence of scatter and increased radiation dose rates beyond the line-of-sight of the source, where virtually no transmission is expected through the tunnel materials. The final part of this project was implementing the modeling techniques into real world threat scenarios for subterranean infrastructure. Two models of a full sized underground roadway were completed using two known radiological exposure device threat materials, Cs-137 and Co-60. Both models resulted in similarly shaped radiation fields and confirmed that the near wall of a crossing roadway offered lower radiation dose rates than the far wall upon approach. These findings could prove useful to decision makers facing a subsurface infrastructure CBRN incident and could lead to the development of tools that can be implemented into emergency preparedness framework.
Keywords: gamma radiation; radiation streaming; CBRN; skyshine; radiation